2018
DOI: 10.1161/hypertensionaha.118.11290
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mitochondrial Dysfunction and Reactive Oxygen Species in Mediating Hypertension in the Reduced Uterine Perfusion Pressure Rat Model of Preeclampsia

Abstract: Placental ischemia is believed to be the initial event in the development of preeclampsia. Mitochondrial dysfunction is a cause of reactive oxygen species (ROS) generation and oxidative stress, however, there are not many studies examining the role of mitochondrial ROS in the pathology of preeclampsia. The purpose of this study was to not only examine the effect of placental ischemia on mitochondrial-mediated oxidative stress in reduced uterine perfusion pressure (RUPP) rat model of preeclampsia but to also ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
162
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(181 citation statements)
references
References 43 publications
15
162
0
1
Order By: Relevance
“…Damaged mitochondria induce cytotoxicity by producing superoxide radicals from the abnormal electron transport chain, and mitochondria are also vulnerable to ROS 35,36 . To detect whether the maintenance of mitochondrial quality was due to the inhibition of mtROS production, we used MitoTEMPO, a specific mtROS scavenger 37,38 , for treatment of liver I/R injury. Similar to previous finding reported by Sang et al, we found that Mito-TEMPO not only inhibited mtROS accumulation but also mitigated I/R-induced liver damage, as evidenced by a reduction in the level of serum hepatic enzymes and improvement in liver pathology 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Damaged mitochondria induce cytotoxicity by producing superoxide radicals from the abnormal electron transport chain, and mitochondria are also vulnerable to ROS 35,36 . To detect whether the maintenance of mitochondrial quality was due to the inhibition of mtROS production, we used MitoTEMPO, a specific mtROS scavenger 37,38 , for treatment of liver I/R injury. Similar to previous finding reported by Sang et al, we found that Mito-TEMPO not only inhibited mtROS accumulation but also mitigated I/R-induced liver damage, as evidenced by a reduction in the level of serum hepatic enzymes and improvement in liver pathology 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, endothelial dysfunction is considered an early independent predictor of CVDs. Extensive cellular and molecular studies have identified putative mediators, which include increased oxidative stress, inflammation, mitochondrial dysfunction, and endothelial cell (EC) apoptosis (Hou et al, ; Kroller‐Schon et al, ; Vaka et al, ), that participate in the progression of endothelial dysfunction. Among these various functional events, oxidative stress seems to be upstream of the cascade (Forstermann, Xia, & Li, ; McSweeney, Warabi, & Siow, ; Munzel et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic alterations relevant to the mitochondrial respiratory chain function and fatty acid oxidation have been reported previously in placentas from women with pre‐eclampsia, where morphological abnormalities of mitochondria were also noted . Recently, impaired mitochondrial function has been demonstrated to play an important role in the development of hypertension and reduced fetal weight in a rat model of pre‐eclampsia …”
Section: Discussionmentioning
confidence: 64%